Ecology of a Two-barred Crossbill (Loxia leucoptera) irruption to Norway in 2019–20: altitudinal migration and interspecific habitat differences - Dale, Svein (Ornis Norvegica, 2021)
Cover photo: A male Two-barred Crossbill (Loxia leucoptera). Photo: Frode Falkenberg. Two-barred Crossbills (Loxia leucoptera) have cyclic irruptions to Norway, but are generally uncommon and breeding is rare. Here I analyse data on a large irruption occurring in 2019–20 to assess the magnitude of the irruption and the ecological niche of the species. The irruption lasted one year, starting in July 2019 and ending in June 2020. Total numbers reported by birdwatchers to the website of the National Biodiversity Information Centre in Norway were ca. 7,000 individuals. Breeding indications were reported from nearly 100 sites. Analyses of elevation of records indicated that birds were often seen at low elevations before the breeding season in February–June, but moved to higher elevations during the breeding season. In a focal study area in SE Norway, breeding season surveys along elevational gradients indicated that Two-barred Crossbills occurred at higher elevations, and often close to summits of hills, perhaps representing preferences for more open forest habitats. Two-barred Crossbills often co-occurred with other seed-eating bird species, but presence was more closely related to numbers of Common Redpoll (Acanthis flammea), than to Eurasian Siskin (Spinus spinus) or cogeneric Common Crossbill (L. curvirostra). Similarly, the Common Redpoll also increased strongly in abundance with elevation, whereas the other two species did so to a lesser degree. These data suggest that the Two-barred Crossbill favors montane forests during the breeding season, and thereby has a different niche than the Common Crossbill which is distributed more widely across all elevations.